Die intrinsieke verband tussen opvoeding en spiritualiteit - Walt, J. L. van der (Koers, 2008)
The intrinsic relationship between education and spirituality After having researched the phenomenon of (especially young) people turning their backs on mainstream religions and finding refuge in “new” forms of spirituality, the authors concluded that, as always, the education of children cannot be done justice to unless attention is also devoted to the development of their spirituality. To defend this contention, they firstly analyse religion as a phenomenon. They find it to be multi-layered, with spirituality forming the innermost layer. They then discuss the emergence of “new” forms of spirituality and find them to be alien to the Biblical concept of spirituality. After discussing the intrinsic link between education and both the “new” and the Biblical forms of spirituality, the authors find their initial conclusion to have been vindicated.